A cognitive-pragmatic perspective on apologies in English and Ukrainian discourse - Shevchenko, Iryna; Gutorov, Volodymyr; Шевченко, Ірина Семенівна; Гуторов, Володимир Олександрович (Trnava : University of SS Cyril and Methodius in Trnava, 2019)
Apologies are interactional social-cultural discourse rituals rooted in intersubjectivity. Their corrective and preventive cognitive-pragmatic types have different scenarios. As conventional hybrid expressive-and-requestive speech acts, they have pragma-semantic subtypes, which realize negative politeness. English and Ukrainian apologies share common cognitive-pragmatic types but differ in pragma-semantic subtypes and linguistic realization.
Keywords: apology; cognitive-pragmatic paradigm; intersubjectivity; frame scenario; English; Ukrainian